Marketing Strategies in Nanomaterials for Sensor Applications: Bridging Lab to Market - Anoop Singh; Eliyash Ahmed; Mehrajud Din Rather; Atchaya Sundararajan; Alka Sharma; Farah S. Choudhary; Ashok K. Sundramoorthy; Saurav Dixit; Nikolai Ivanovich Vatin; Sandeep Arya (Global Challenges)
Abstract Nanomaterials have revolutionized sensor technology by offering enhanced sensitivity, selectivity, and miniaturization capabilities. However, the commercialization of nanomaterial‐based sensors remains challenging due to the complexities involved in bridging laboratory innovations to market‐ready products. This review article explores the various marketing strategies that can facilitate the successful commercialization of nanomaterials for sensor applications. It emphasizes the importance of understanding market needs, regulatory landscapes, and the value proposition of nanomaterials over traditional materials. The study also highlights the role of strategic partnerships, intellectual property management, and customer education in overcoming market entry barriers. Through a comprehensive analysis of case studies and industry practices, this review provides a framework for companies and researchers to effectively transition from lab‐scale innovations to commercially viable sensor products. The findings suggest that a well‐rounded marketing strategy, combined with robust product development and stakeholder engagement, is crucial for capitalizing on the unique benefits of nanomaterials in sensor applications.